Hadith #7 - The Forty Hadith Qudsi - Uqbah ibn Amir (The Forty Hadith Qudsi)
On the authority of Uqbah ibn Amir (may Allah be pleased with him), who said: I heard the messenger of Allah (ﷺ) say: Your Lord delights at a shepherd who, on the peak of a mountain crag, gives the call to prayer and prays. Then Allah (glorified and exalted be He) say: Look at this servant of Mine, he gives the call to prayer and performs the prayers; he is in awe of Me. I have forgiven My servant [his sins] and have admitted him to Paradise.
Grade: Hasan